Sustainability, Financial Performance dan Implikasinya terhadap Audit Outcomes: Studi Pada Indonesian Mining Companies - Ros Nirwana; Suzi Suzanna; Arifia Nurriqli; Siti Fatimah; Maria Anatasia (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to examine the effect of sustainability commitment and financial performance on audit outcomes in mining companies in Indonesia. Sustainability commitment is proxied by environmental performance measured using the PROPER score and the amount of Corporate Social Responsibility (CSR) expenditure, while financial performance is measured by Return on Assets (ROA). Audit outcomes are represented by audit quality, proxied by the use of Big Four public accounting firms, and audit delay, measured as the number of days between the fiscal year-end and the auditor’s report date. Method: This study employs a quantitative approach using panel data from 19 mining companies listed on the BEI over the period 2020–2024, resulting in 95 firm-year observations. Data analysis is conducted using random-effects panel logistic regression to examine audit quality and fixed-effects panel regression with robust standard errors to analyze audit delay. All statistical analyses are performed using STATA version 17. Finding: The results indicate that PROPER, CSR expenditure, and ROA do not have a significant effect on audit quality, either partially or simultaneously. In contrast, with respect to audit delay, PROPER and CSR expenditure have a negative and significant effect, while ROA does not show a significant effect. Simultaneously, PROPER, CSR expenditure, and ROA are found to significantly affect audit delay. These findings suggest that corporate sustainability commitment particularly environmental performance and the realization of CSR expenditure plays an important role in improving audit efficiency and the timeliness of financial reporting, but has not yet become a primary consideration for auditors in determining audit quality. This study contributes to the empirical literature by enriching the understanding of the relationship between corporate sustainability and audit outcomes within the context of the Indonesian mining industry. Novelty: The novelty of this study lies in the simultaneous use of two sustainability commitment indicators, namely the PROPER score and CSR expenditure, which provide a more comprehensive representation of corporate sustainability commitment. In addition, this study examines two dimensions of audit outcomes, namely audit quality and audit delay, in Indonesian mining companies during the 2020–2024 period, a sector characterized by high environmental risk and regulatory pressure.